Reformar el artículo 4 de la ley orgánica de defensa del consumidor, para proteger los derechos de los consumidores - Álvarez Cabrera, Miguel Reinaldo (2017)
The Constitution of the Republic, Section Ninth says about users and consumers, where Article 52 specifically states: "Right to goods and services of the highest quality.- People have the right to dispose of goods and services optimum quality and to choose freely and to accurate and not misleading about its content and features. The law establishes the quality control mechanisms and procedures for defense of consumers and consumers; and penalties for violation of these rights, reparation and compensation for defects, damage or poor quality of goods and services, and the interruption of public services that was not caused by accident or force majeure " Ie the state is called upon to ensure compliance with the rights of users through its institutions its powers, functions, legislation and public policy have responsibilities for the protection and promotion of consumer rights. Every act of consumption, evidently implies entering a marketing process, for which information on companies is required at first and then to the consumer, a fact that serves to meet the needs of both parties, whose aim is to decide by the lower possible risk in the sale and purchase of goods and services.